Constraints to domestic ocean cruise participation among higher income Chinese adults. (2nd May 2019) - Tang, Chuanzhong; Weaver, David; Shi, Fangfang; Huang, Ming‐Feng; Liu, Yang
Abstract: The study identifies barriers to participation in cruises from domestic homeports among higher income Chinese adults. Results from 775 respondents extend leisure constraints theory by revealing that "structural" constraints (lack of knowledge, time, and money) most influence intentions not to cruise even for these wealthier consumers, whereas "not‐an‐option" constraints (disinterest due to previous cruising experience, intentions to cruise from a foreign homeport) are least influential. "Personal" factors (lack of companions and fears about safety, boredom, and seasickness) are moderately important. Six identified clusters include a large normative "moderate‐constraint" cluster, small "low‐potential" and "high‐potential" segments, and several specialized segments.